Calidad de datos en archivos RDF - Quinche Granda, Anabel Stefania (2018)
Abstract:The difficulty of publishing much of the information and supporting the report is also an analysis of the RDF files, which is one of the languages of the semantic web, its role being the specification of knowledge with well-defined semantics. Some RDF files are created without having to have the quality measures established in the semantic web that make it difficult to manage the information optimally. The use of the semantic web has been growing more and more, in the necessary and challenging way, the quality of the data in the semantic web. The consistency, accuracy and integrity of the web have been recognized as a major problem in the latest trends. The search for information at various levels of data quality on the web can produce inaccurate or irrelevant results for this purpose with the aim of improving the creation and publication of RDFs. Research is done on studies that validate RDFs to develop an application that validates quality in these files.